Role of AI chatbots in education - Hamid Mahdavifard (Journal of Medical Education and Development)
The traditional education system faces many problems, including overcrowded classes, lack of attention to students, different learning speeds and styles, and trying to keep up with the rapid evolution of technology and information. As the educational landscape changes over time, the emergence of AI-based chatbots appears as a promising solution to some of the emerging issues in education. Some educational institutions are increasingly turning to AI-based chatbots, while others are more cautious and in no rush to adopt modern learning environments (1).